2019
DOI: 10.3390/environments6060069
|View full text |Cite
|
Sign up to set email alerts
|

Phytostabilization of Zn and Cd in Mine Soil Using Corn in Combination with Biochars and Manure-Based Compost

Abstract: Mining activities could produce a large volume of spoils, waste rocks, and tailings, which are usually deposited at the surface and become a source of metal pollution. Phytostabilization of the mine spoils could limit the spread of these heavy metals. Phytostabilization can be enhanced by using soil amendments such as manure-based biochars capable of immobilizing metal(loid)s when combined with plant species that are tolerant of high levels of contaminants while simultaneously improving properties of mine soil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
0
17
0
1
Order By: Relevance
“…According toŻołnowski et al [43] and Lam et al [44], the application of an organic substance into soil reduces the bioconcentration factors for trace elements in plants, including in maize. In a study by Sigua et al [45], manure had a similar effect on the bioconcentration factor values for Zn and Cd in the shoots and roots of maize. This was confirmed in the author's own study, in which compost reduced the concentrations of most trace elements in maize; the exception was Ni.…”
Section: The Effect Of Amendments On Plants Cultivated On Soil Contaminated With Coppermentioning
confidence: 77%
“…According toŻołnowski et al [43] and Lam et al [44], the application of an organic substance into soil reduces the bioconcentration factors for trace elements in plants, including in maize. In a study by Sigua et al [45], manure had a similar effect on the bioconcentration factor values for Zn and Cd in the shoots and roots of maize. This was confirmed in the author's own study, in which compost reduced the concentrations of most trace elements in maize; the exception was Ni.…”
Section: The Effect Of Amendments On Plants Cultivated On Soil Contaminated With Coppermentioning
confidence: 77%
“…Agnello et al [114] compared biological processes such as natural attenuation, bioaugmentation, and phytoremediation. They found that bioaugmentation-assisted phytoremediation optimizes the synergy effect of plants and microorganisms, improving the removal of heavy metals and metalloids [115].…”
Section: Phytoextractionmentioning
confidence: 99%
“…Phytostabilization is an efficient remediation approach that includes establishing plant cover by using species that can stabilize pollutants in the root zone (e.g., roots and rhizosphere) by accumulation or precipitation and, thus, reduce their mobility and bioaccessibility [13,14]. Hence, species that are tolerant to high contamination levels and, at the same time, present an extensive fasciculated root system, rapid growth and establishment, high longevity, easy maintenance, good adaptation to contamination and below-ground accumulation of metals are the best candidates for phytostabilization [14][15][16]. The selection of the appropriate amendment or combination of amendments is also crucial for the success of the remediation process [1,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, species that are tolerant to high contamination levels and, at the same time, present an extensive fasciculated root system, rapid growth and establishment, high longevity, easy maintenance, good adaptation to contamination and below-ground accumulation of metals are the best candidates for phytostabilization [14][15][16]. The selection of the appropriate amendment or combination of amendments is also crucial for the success of the remediation process [1,14,17]. The interactions between the selected amendment and plant species and the subsequent relationship with the target contaminants will condition the restoration process.…”
Section: Introductionmentioning
confidence: 99%